Biotransformations with nitrilases - Martínková, Ludmila; Kren, Vladimír (Current opinion in chemical biology, 2010)
The range of possible nitrilase applications has been recently broadened but in most cases the parameters of the reactions need to be improved to establish viable industrial processes. To achieve this goal, several methods have been used, primarily in screening for enzymes from new sources, enzyme improvement, substrate structure modification, medium engineering, and variation in process parameters. New nitrilases have been obtained by for example genome mining and the metagenomic approach. Protein engineering revealed targets for altering substrate specificity, activity or enantioselectivity, and for changing the acid:amide ratio in the nitrilase product. Variation in substrate structure proved to be another means to modify the enantioselectivity and chemoselectivity of the reactions. The utility of nitrilases will be increased further if they can be applied in combination with other enzymes or chemical catalysts without laborious intermediate isolation. Such processes have been developed, for instance, for the synthesis of (S)-mandelic acid, (S)-mandeloamide or glycolic acid.
Keywords: biotransformace; Bacterial Proteins; Biotransformation; Amides; aminohydrolasy; Fungal Proteins; Amino Acids; amidy; proteinové inženýrství; Protein Engineering; fungální proteiny; bakteriální proteiny; Aminohydrolases; aminokyseliny